Role of Few Gram Positive and Gram Negative Bacteria Isolated from UTI Patients - Razaq, Mortadha H.; Abas S. Hason; Oyla Y. Khelaf; Muhammed H. Jasim; Muhammed Abd A. Dalaf (Scientific Journal of Medical Research, 2023)
This study was conducted from 10/1/2021 to 25/4/2021 at Al-Husseini Teaching Hospital. This study aimed to know the role of gram-negative and gram-positive bacteria in urinary tract infections and the sensitivity and resistance of these bacteria to antibiotics. During this period (60) specimens were collected for different age groups between (more than 60) years and for both sexes. The specimens were cultured on different culture media in regular conditions and diagnosed laboratory. Bacterial cultures were positive in 83.3%, while 16.6% of patients revealed negative in culture. Results of the study showed 29 (58%) isolates of G+ve bacteria were obtained, which included Staphylococcus aureus, Enterococcus faecalis and Streptococcus agalactiae, while 21 (42%) isolates of G-ve bacteria were obtained, which is included E. coli, Pseudomonas aeruginosae, and Proteus mirabilis. The results of the bacterial isolation showed a predominance of S. aureus bacteria by 36%, followed by E. coli by 32%, followed by E. faecalis by 20%, P. aeruginosa by 6%, P. mirabilis by 4%, and finally, S. agalactiae by 2%. The study showed that the rate of infection of females is more compared to males, where the percentage of females was 56%, while males were 44%, and the highest percentage of infection was in the age group (1–35) years; where the infection rate among younger age groups was higher than with the older groups. Sensitivity tests were conducted for the most important bacterial isolates that cause the disease towards some antibiotics. In this study G+ve bacteria, including S. aureus showed high rate of sensitivity to amikacin (100%), levofloxacin (77.8%), gentamycin (38.9%), and cefixime (5.6%). E. faecalis was sensitive to levofloxacin (30%), amikacin (50%), cefotaxime (10%) and gentamycin (40%). S. agalactiae showed sensitivity to levofloxacin, amikacin and gentamycin (100%). In comparison, G-ve bacteria, including E. coli showed high rate of sensitivity for azithromycin (75%), cefotaxime (62.5%), amikacin (37.5%), levofloxacin with percentage (25%), ceftriaxone (6.25%) and gentamycin (18.75%). P. aeruginosa showed a high sensitivity rate to azithromycin (100%), and levofloxacin (33.3%). While P. mirabilis showed a high sensitivity rate to azithromycin (100%), amikacin and cefotaxime (50%).